Insulin‐like growth factor‐binding protein 3 inhibits angiotensin II‐induced aortic smooth muscle cell phenotypic switch and matrix metalloproteinase expression. Issue 11 (30th September 2020) - Chen, Suwei; Chen, Hong; Zhong, Yongliang; Ge, Yipeng; Li, Chengnan; Qiao, Zhiyu; Zhu, Junming
Abstract : New Findings: What is the central question of this study? Insulin‐like growth factor 1 and its major binding protein insulin‐like growth factor binding protein 3 (IGFBP3) are involved in collagen deregulation in several cardiovascular diseases: what is the role of IGFBP3 in thoracic aortic dissection and does it regulate aortic smooth muscle cells' phenotypic switch? What is the main finding and its importance? IGFBP3 inhibits aortic smooth muscle cells' phenotypic switch from a contractile to a synthetic phenotype, decreases matrix metalloproteinase 9 activation and suppresses elastin degradation. These findings provide a better understanding of the pathogenesis of thoracic aortic dissection. Abstract: Thoracic aortic dissection (TAD) is characterized by aortic media degeneration and is a highly lethal disease. An aortic smooth muscle cell (AoSMC) phenotypic switch is considered a key pathophysiological change in TAD. Insulin‐like growth factor binding protein 3 (IGFBP3) was found to be downregulated in aortic tissues of TAD patients. The present work aimed to study the function of IGFBP3 in AoSMCs' phenotypic switch and matrix metalloproteinase (MMP) expression. We established a mouse model of TAD by angiotensin (Ang) II infusion to β‐aminopropionitrile‐administrated mice, and found decreased IGFBP3 expression accompanied by aortic dilatation and elastin degradation in vivo . Further, mouse (m)AoSMCs were isolated from mouse thoracic aorta and treated with Ang II. Ang II induced downregulation of IGFBP3 in vitro . To further study the function of IGFBP3, primary mAoSMCs were infected with adenovirus expressing IGFBP3 followed by Ang II induction. Enforced upregulation of IGFBP3 decreased MMP9 expression and activation as well as increasing tissue inhibitor of metalloproteinase (TIMP) 1 expression in Ang II‐induced mAoSMCs. No difference was observed in MMP2 and TIMP3 expression. IGFBP3 suppressed subsequent Ang II‐induced elastin degradation in vitro . IGFBP3 inhibited Ang II‐induced mAoSMCs' phenotypic switch as evidenced by increased smooth muscle actin α‐2 (ACTA2) and myosin heavy chain 11 (MYH11) expression and decreased secreted phosphoprotein 1 (SPP1) and vimentin expression. Taken together, the present study demonstrates the role of IGFBP3 in preserving AoSMCs' contractile state and reducing MMP9 activation and thus promoting elastic fibre synthesis, which provides a better understanding of the pathogenesis of TAD. Abstract :